The impact of adverse childhood experiences on an urban pediatric population - Burke, Nadine J.; Hellman, Julia L.; Scott, Brandon G.; Weems, Carl F.; Carrion, Victor G. (Child abuse & neglect, 2011)
The goal of this study was to investigate the adverse childhood experiences (ACEs) in youth in a low-income, urban community. Data from a retrospective chart review of 701 subjects from the Bayview Child Health Center in San Francisco are presented. Medical chart documentation of ACEs as defined in previous studies were coded and each ACE criterion endorsed by a traumatic event received a score of 1 (range = 0–9). This study reports on the prevalence of various ACE categories in this population, as well as the association between ACE score and two pediatric problems: learning/behavior problems and body mass index (BMI) ≥ 85% (i.e., overweight or obese). The majority of subjects (67.2%, N = 471) had experienced 1 or more categories of adverse childhood experiences (ACE ≥ 1) and 12.0% ( N = 84) had experienced 4 or more ACEs (ACE ≥ 4). Increased ACE scores correlated with increased risk of learning/behavior problems and obesity. There was a significant prevalence of endorsed ACE categories in this urban population. Exposure to 4 or greater ACE categories was associated with increased risk for learning/behavior problems, as well as obesity. Results from this study demonstrate the need both for screening of ACEs among youth in urban areas and for developing effective primary prevention and intervention models.